China enters WTO : pursuing symbiosis with the global economy - Yamazawa, Ippei (Institute of Developing Economies. Japan External Trade Organization ChibaJP, 2001)
Focuses on the transformation of domestic institutions in China on its accession to the WTO, its influences on major sectors and foreign direct investment (FDI). Analyses the implications on China's economic development and its external economic relations. Looks at the impact of China's WTO accession on the economic relationship between China and other economies in the Asia-Pacific region. Examines how China's role in the region's international division of labour will be affected, and what challenges China and other economies in the region will face as China is successfully integrated into the global economy.